Processamento ultrarrápido do eletrólito sólido Na₃Zr₂Si₂PO₁₂ pela técnica de reactive flash sintering - Campos, Leonardo Jesus de (Universidade Federal de São Carlos, 2026)
Solid-state sodium batteries have attracted increasing interest due to the abundance and low production cost of sodium, as well as the potential for improved safety compared to batteries employing flammable liquid electrolytes. Among the most promising solid electrolytes is Na3Zr2Si2PO12 (NZSP), a member of the NaSICON family, which exhibits high ionic conductivity. However, its conventional processing requires calcination and sintering steps at high temperatures and long dwell times, promoting sodium and phosphorus volatilization and increasing energy consumption. In this work, Reactive Flash Sintering (RFS) was investigated as an alternative route to promote both NaSICON phase formation and densification of NZSP in a single processing step. The effects of the maximum applied power, dwell time, and power ramp rate on phase formation, microstructure, and electrical properties were systematically evaluated. The results demonstrated that the processing condition of 150 mW mm-3, combined with a power ramp rate of 30 mW mm-3 min-1 and a dwell time of 15 min, enabled the production of samples with a relative density of approximately 96%, a total ionic conductivity of 1.14 ± 0.11 mS cm-1, and an activation energy of 0.30 ± 0.01 eV. In comparison, conventionally processed samples exhibited lower conductivity (0.75 ± 0.02 mS cm-1) and higher activation energy (0.35 ± 0.01 eV). The use of sacrificial powder during conventional sintering, aiming to reduce the loss of volatiles, such as sodium or phosphorus, at high temperatures, increased the conductivity to values comparable to those obtained by RFS, indicating that the main advantage of the electric field-assisted process is associated with the reduction of volatile species losses during processing. The results demonstrate, for the first time, the feasibility of producing NZSP electrolytes by Reactive Flash Sintering directly from unreacted precursor powders, highlighting the potential of this technique as a rapid and energy-efficient route for the fabrication of solid electrolytes.
Ultrafast processing of the Na3Zr2Si2PO12 solid electrolyte via reactive flash sintering
Keywords: Baterias de estado sólido; Condução por íons sódio; Reactive flash sintering; NaSICON; Eletrólitos sólidos; Solid-state batteries; Sodium-ion conduction; Reactive flash sintering; NaSICON; Solid electrolytes; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; 7. Energia limpa e acessível